2023
DOI: 10.1007/s11157-023-09675-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessing metal contamination and speciation in sewage sludge: implications for soil application and environmental risk

Jianting Feng,
Ian T. Burke,
Xiaohui Chen
et al.

Abstract: Based on the most recently published data, we definitively estimated that the annual global production of sewage sludge may rise from ~ 53 million tons dry solids currently to ~ 160 million tons if global wastewater were to be treated to a similar level as in the 27 European Union countries/UK. It is widely accepted that the agricultural application is a beneficial way to recycle the abundant organic matter and plant nutrients in sewage sludge. However, land application may need to be limited due to the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 208 publications
0
0
0
Order By: Relevance
“…The analysis showed that the trend of metal concentra- As can be observed, the results varied slightly, but in all cases, Zn and Cu showed the highest concentrations and Cd the lowest. Overall, the distribution pattern found in the WWTPs was similar to that found for sludge produced in other WWTPs [44,[50][51][52].…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…The analysis showed that the trend of metal concentra- As can be observed, the results varied slightly, but in all cases, Zn and Cu showed the highest concentrations and Cd the lowest. Overall, the distribution pattern found in the WWTPs was similar to that found for sludge produced in other WWTPs [44,[50][51][52].…”
Section: Resultssupporting
confidence: 75%
“…Metal concentrations in sludge can vary from country to country, but typical metal concentrations in all countries are similar to those presented in this assessment [9,[51][52][53][54][55][56][57][58][59][60][61]. However, it should be noted that metal concentrations in European and Japanese sludge are generally lower than in sludge from other countries [50].…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Globally, wastewater treatment facilities currently generate approximately 53 million tons of dry sewage sludge annually (Feng et al, 2023). If wastewater treatment practices were similar to those in the European Union/the United Kingdom, this sludge output would potentially increase to 160 million tons yearly.…”
Section: Introductionmentioning
confidence: 99%
“…The release of trace elements, especially heavy metals and metalloids, into the environment as a result of industrial development and urbanization is a global problem today [13]. The main amount of metals comes from industrial wastewater [14]. However, domestic and non-industrial wastewater from industrial enterprises entering municipal wastewater treatment plants may also contain significant amounts of trace elements.…”
Section: Introductionmentioning
confidence: 99%